2022
DOI: 10.1155/2022/4478444
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Electroacupuncture for Pain Control in Herpes Zoster: A Systematic Review and Meta-Analysis

Abstract: Introduction. Herpes zoster is caused by the reactivation of the latent varicella-zoster virus, which leads to acute pain that may disturb routine activities and affect patients’ quality of life. Electroacupuncture (EA) has been commonly used for treating herpetic pain in clinical treatment. However, no relevant studies have been performed to evaluate the efficacy and safety of EA for acute control in herpetic neuralgia patients. The purpose of the current study was to conduct a systematic review and meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Electroacupuncture could activate a variety of bioactive chemicals and desensitized peripheral nociceptors, [ 96 ] thereby blocking pain caused by acute HZ. [ 97 ] PC has been found to be effective in reducing serum substance P (SP) levels and relieving symptoms in patients with HZ at the acute stage. [ 98 ] FN is capable of alleviating the pain of acute HZ probably by inhibiting the release of inflammatory cytokines and reducing the level of pain mediators such as SP.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture could activate a variety of bioactive chemicals and desensitized peripheral nociceptors, [ 96 ] thereby blocking pain caused by acute HZ. [ 97 ] PC has been found to be effective in reducing serum substance P (SP) levels and relieving symptoms in patients with HZ at the acute stage. [ 98 ] FN is capable of alleviating the pain of acute HZ probably by inhibiting the release of inflammatory cytokines and reducing the level of pain mediators such as SP.…”
Section: Discussionmentioning
confidence: 99%
“…18 , 19 Results from some recent studies have demonstrated that electroacupuncture can be effective in treating the acute pain of Herpes Zoster and low-level laser therapy can reduce the incidence of PHN. 2 , 20 Moreover, there are some case reports documenting the efficacy of toxins in patients with PHN refractory to conventional treatments in terms of VAS score reduction, with an analgesic duration ranging from 52 to 64 days and a good degree of tolerability. 14 , 21…”
Section: Discussionmentioning
confidence: 99%
“… 12 Furthermore, EA therapy for acute herpes zoster-associated pain also surpasses conventional approaches such as oral antiviral medications. 68 …”
Section: Discussionmentioning
confidence: 99%